Cooling strongly self-organized particles using adiabatic demagnetization - Jäger, Simon B. (Frontiers in Quantum Science and Technology, 2025)
This study examines the dynamics of polarizable particles, coupled to a lossy cavity mode, that are transversally driven by a laser. The analysis is performed in a regime where the cavity linewidth exceeds the recoil frequency by several orders of magnitude. Using a two-stage cooling protocol, we show that the particles’ kinetic energy can be reduced to the recoil energy. This cooling protocol relies in its first stage on a high laser power such that the particles cool into a strongly self-organized pattern. This can be seen as a strongly magnetized state. In a second stage, we adiabatically ramp down the laser intensity such that the particles’ kinetic energy is transferred to their potential energy and the particles are “demagnetized”. In this second stage, we optimize the ramping speed, which needs to be fast enough to avoid unwanted heating and slow enough such that the dynamics remains approximately adiabatic.